Mendeteksi Kehamilan Dini Melalui Pemeriksaan USG Uterus - Nurbeti, Nurbeti; Dardi, Satriana; Mora, Mora; Mustika, Dian Nintyasari; Purwanti, indri astuti (ADPERTISI, 2024)
Health education on Ultrasonography (USG) has never been carried out in Bonto Mate'ne Village, Marusu District, Maros Regency, South Sulawesi. Even though knowledge about ultrasound is very important to prevent stunting from early pregnancy. Therefore, the aim of this activity is to provide education on detecting early pregnancy through ultrasound examination of the uterus. The methods used in this activity are lecture, question and answer, and pretest-posttest to measure the increase in participants' knowledge. The number of participants was 15 people, but 11 people took the pretest and posttest. The implementation of activities ran smoothly and orderly. Participants were very enthusiastic and active. There were 5 participants who asked questions and they were answered satisfactorily. The posttest results also showed that all participants experienced an increase in knowledge.